DESIGN, DEVELOPMENT AND EVALUATION OF FLUCONAZOLE TOPICAL GEL - Das, Sudipta; Samanta, Arnab; Bose, Ananya (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The present study was designed to formulate and evaluate Fluconazole topical gel. Methods: The gel was formulated by using polymer sodium carboxy methyl cellulose in different ratio. The drug-excipient compatibility studies were confirmed by differential scanning calorimetry analysis. The evaluation of formulated fluconazole topical gel was carried out for physical appearance, pH-value, spreadability, rheological behavior, drug content and in-vitro release study. Results: The rheological behavior of the prepared gels showed a pseudo plastic flow, which is a good characteristic of topical pharmaceutical gels. The formulated gel showed good physical characteristic and release profile. The release data was fitted into different kinetics equations by regression analysis. Stability studies showed no significant change in physical appearance, rheological properties and drug release upon storage for 3 months at ambient condition. Conclusion: Fluconazole was successfully incorporated into the different topical gel formulations, and the developed formula could be very promising topical alternative for the treatment of skin fungal infection. Keywords: Fluconazole, Differential scanning calorimetry, Sodium carboxymethyl cellulose, Gel, Kinetic.